Between a Rock and a Hard Place: How to Use Antithrombotics in Patients Undergoing Transcatheter Aortic Valve Replacement. Issue 2 (2019) - Grossman, Kelsey; Williams, Mathew R; Ibrahim, Homam
No abstract available